Approximation of the $| x |^r$ function and its derivatives - Shvai, A. I.; Antonyuk, P. E.; Dzyadyk, S. Yu.; Zaritskaya, Z. V. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
We consider the problem of an effective approximation of derivatives of the function $|x|^r,r>1$, in $C[-1,1]$ with the aid of polynomials introduced by V. K. Dzyadyk.